2014
DOI: 10.1038/npp.2014.92
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Linkage and Association of GABRB3 and GABRA5 to Panic Disorder

Abstract: Panic disorder (PD) is a debilitating anxiety disorder characterized by episodes of intense fear with autonomic and psychological symptoms that lead to behavioral impairment. A convergence of genetic and biological evidence implicates gamma-aminobutyric acid type A receptor subunits on chromosome 15q12 as candidate genes for PD. This study investigated 120 Caucasian, multiplex PD pedigrees using regional microsatellites (chr15q11-13) and found support for linkage (logarithm of odds (LOD) X2), with a prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Further, meta-analyses reveal reduced cortical thickness in depressed patients within medial prefrontal and temporal regions 55 that show strong limbic cortico-striatal correlations within the current study. Our analyses additionally revealed genes implicated in ventral-striatal mediated behaviors, including OXT, GABRA3 , GABRA5 , GABRB1 , and GABRB3 , which have previously been linked to mesolimbic reward circuitry and risk for associated disorders 56 58 . Of note, 14% of the 505 AHBA limbic cortico-striatal genes have no established gene ontology annotation (count = 71), supporting the use of gene co-expression analyses as a tool for nominating genetic markers of behavior and mental illness.…”
Section: Discussionmentioning
confidence: 79%
“…Further, meta-analyses reveal reduced cortical thickness in depressed patients within medial prefrontal and temporal regions 55 that show strong limbic cortico-striatal correlations within the current study. Our analyses additionally revealed genes implicated in ventral-striatal mediated behaviors, including OXT, GABRA3 , GABRA5 , GABRB1 , and GABRB3 , which have previously been linked to mesolimbic reward circuitry and risk for associated disorders 56 58 . Of note, 14% of the 505 AHBA limbic cortico-striatal genes have no established gene ontology annotation (count = 71), supporting the use of gene co-expression analyses as a tool for nominating genetic markers of behavior and mental illness.…”
Section: Discussionmentioning
confidence: 79%
“…This would account for the shared associations of each of these disorders with gamma-aminobutyric acid and endocannabanoid receptor physiology, 7 , 67 , 68 , 69 , 70 and the fact that benzodiazepines and exogenous cannabinoid use may be effective in aborting acute CVS attacks, 1 , 13 migraines, 70 seizures, 65 , 67 and panic attacks. 69 It would account for the utility of triptan medications in aborting migraines and CVS attacks. 1 , 18 , 55 It may also explain some reports of beneficial effects of nonsteroidal anti-inflammatory drugs in treating CVS.…”
Section: Introductionmentioning
confidence: 99%
“…The other genes in the distal chromosome 15q11.2‐q13 region include gamma aminobutyric acid (GABA) receptor subunits GABRB3, GABRA5 , and GABRG3 , which are not imprinted. Alterations in the GABAergic systems are associated with hunger (Turenius et al, ), anxiety (Hodges et al, ), OC symptoms, and addiction (Stephens, King, Lambert, Belelli, & Duka, ). While hypoactivity may contribute to obesity in PWS (Dhar et al, ), nearly 60% of our patients were reported to be hyperactive and perhaps this sheds some light on differences in metabolic phenotype in AS compared to PWS.…”
Section: Discussionmentioning
confidence: 99%